Managing a non-profit organization: The case of Arab trading and contracting company - Abdallah, Mohamad Ali; Younis, Joumana (Open Science Journal, 2023)
Under the current situation in Lebanon, it has become prudent for people and organizations to take the government position. Such organizations started initiating programs that help people in educational, living situating, and other forms of social aiding. Arab Trading and Contracting Company (ATC) was one of the pioneer’s non-profit organizations (NPO) helping the Lebanese people through essential worldwide programs. ATC used a combination of managerial steps in addition to decentralized structure to cope with the needed requirements of sustainability. Moreover, ATC set a training & development and innovative strategy to assure the continuity of the organization. Finally, the case study stated the main strategy that ATC embraces, which is creating a for-profit organizations to fund its NPO.